Novos ensaios e estudos cinéticos da endopeptidase neutra (EC 3.4.24.11): influência do par de anginina em P'2 P'3 na degradação fisiológica dos peptideos opioides que contem encefalinas - Medeiros, Maria Angelina da Silva (1997)
Neutral endopeptidase (NEP, enkephalinase, neprilysin, EC 3.4.24.11) is a broadly specific zinc metalloendopeptidase which hydrolyzes internai peptide bonds on the amino side of hydrophobic amino acid residues in P j position, being Leu or Phe prefered amino acids. NEP is widely distributed in various tissues, and it is involved in the regulation and metabolism of a variety of biologically active peptides such as substance P, enkephalins, atrial natriuretic factor, bradykinin, gastrin, neurotensin and the chemotatic peptide. lt was found that four intramolecularly quenched fluorogenic peptides containing o-minobenzoyl (Abz) and ethylenediamine 2,4-dinitrophenyl (EDDnp) groups at amino- and carboxyl-terminal amino acid residues, Abz-dRRL- EDDnp, Abz-dRRV-EDDnp, Abz-dRRF-EDDnp and Abz-GGdFLRRV-EDDnp, were selectively hydrolyzed by neutral endopeptidase (NEP) at the Arg-Leu , Arg- Val, Arg-Phe and Arg-Val bonds, respectively. The kinetic parameters for the NEP catalyzed hydrolysis of Abz-dRRL-EDDnp, Abz-dRRV-EDDnp, Abz-dRRF- EDDnp were: Km - 2.8 pM, Acat = 5.3 min'1, kcaXl Km = 2 min'1 pM'1, Km = 3.7 pM, kcat = 5.1 min'1, k^lKm = 1.3 min'1 pM'1 and Km = 5.0 pM, kcai = 7.0 min'1, kcJKm = 1.4 min'1 pM'1, respectively. The high specifícity of these substrates was demonstrated by their total resistance to hydrolysis by metalloproteases [thermolysin, angiotensin-converting enzyme, serineproteases, a-chymotrypsin and proteases present in tissue homogenates from kidney, lung, brain and testis. The blocked amino- and carboxyl-terminal amino acids protected these substrates against the action of aminopeptidases, carboxypeptidases and ACE. Furthermore, dR amino acid ensured a total protection of Abz-dRRL-EDDnp, Abz-dRRF-EDDnp and Abz-dRRF-EDDnp against the action of thermolysin and trypsin. The kinetic parameters for the NEP catalyzed hydrolysis of Abz-GGdFLRRV-EDDnp was: Km = 3.0 pM, k^ = 127 min'1, k^J Km = 42 min1 pM'1. Although Abz- GGdFLRRV-EDDnp also presents a good specifícifíty for NEP, since it is resistant to other metalloendopeptidases such as angiotensin-converting enzyme and thermolysin, it is partially susceptible to degradation by trypsin-like enzymes which may cleave the R-R bond of its sequence. In conclusion, (i) the previously described substrate Abz-GGdFLRRV-EDDnp, which presents the best parameters kinetics, is more suitable than Abz-dRRL-EDDnp, Abz-dRRV-EDDnp and Abz-dRRF-EDDnp for NEP assays in purified enzyme preparations and (ii) the substrates Abz-dRRL- EDDnp, Abz-dRRV-EDDnp and Abz-dRRF-EDDnp, which presents the best specifícity, suits better than Abz-GGdFLRRV-EDDnp for NEP assays in crude enzyme preparations. The presence of the neutral metal!o-endopeptidase 3.4.24.11 activity was investigated by fluorimetTic assay in seminal plasma. NEP was purified to homogeneity from seminal fluid. Enzyme assays were performed with Abz-dRRL- EDDnp, Abz-dRRF-EDDnp e Abz-dRRV-EDDnp. Although the enzyme was previously known to occur exclusively in membrane bound in the human or animal central nervous system, its activity was purified in seminal plasma human. The probable function of NEP in the male genital tract may be related to sperm maturation and proacrosin activation.